VISUALITY OF RACE IN POPULAR CULTURE: TEACHING RACIAL HISTORIES AND ICONOGRAPHY IN MEDIA - Acuff, Joni Boyd; Kraehe, Amelia M. (Dialogue, 7(3), 2020)
The repetition of racist imagery from historical to contemporary popular culture is indicative of a lack of visual culture education among artists, designers, and other creative cultural producers working today. This paper addresses the dearth of resources for teaching visual codes and conventions of racial iconography that are recycled in popular media and contribute to the fabrication of racial differences, maintenance of racial hierarchies, and normalization of white supremacist ideology. Inspired by Critical Race Theory in art and visual culture education, the essay proposes teaching tactics and sites/sights that can support students in developing visual understandings of race in popular culture and the practices of racialized looking it invites. Because popular culture is contested terrain, students can learn to be race-conscious consumers of popular culture today. A deeper awareness of visual codes and conventions can foster critical interpretations and creative responses to popular racial constructions. We suggest key vocabulary for scaffolding dialogue and counter-visual strategies for deconstructing racial images and practices of looking. Keywords: race, representation, popular culture, art, visual culture, racial literacy, critical race theory
Keywords: Type of access: Open Access